PERTUMBUHAN PRODUKTIVITAS PERUSAHAAN MANUFAKTUR INDONESIA DAN PENANAMAN MODAL ASING: PENERAPAN METODE DEKOMPOSISI - Suyanto, Suyanto (Universitas Muhammdaiyah Surakarta, 2012)
This paper examines the productivity growth of Indonesian local firms in relation to foreign direct investment (FDI). Using the survey data of manufacturing firms in Indonesia from 1988 to 2000, the paper decomposes the productivity growth of Indonesian manufacturing firms into three important sources: technical efficiency change, technological progress, and scale efficiency change. The results show that the average total factor productivity (TFP) growth between 1988 and 2000 is 3.51, and the major source contributed to the growth come from technological progress. The interesting finding appears when the data is grouped into foreign firms and domestic firms. It is found that foreign firms have larger productivity growth compared to domestic firms, especially during the period of crisis onwards.